Elevated CD54 expression renders CD4+ T cells susceptible to NK cell-mediated killing. - Chen, X; Chen, H; Zhang, Z; Fu, Y; Han, X; Zhang, Y; Xu, J; Ding, H; Cui, H; Dong, T; Shang, H; Jiang, Y (Oxford University Press, 2019)
A decreased number of CD4+ T cells is a major feature of HIV infection. Here we detected high CD54 expression on CD4+ T cells in HIV-infected individuals, and demonstrate that upregulated CD54 is associated with disease progression in individuals infected with HIV. We also show that CD54 expression leads to the killing of CD4+ T cells by NK cells in vitro, and that this is modulated by NF-κB/p65 signaling. Further, we demonstrate that metformin can suppress CD54 expression on CD4+ T cells by inhibiting NF-κB/p65 phosphorylation; thus, our data suggest that further studies to evaluate the potential role of metformin as adjunctive therapy to reconstitute immune function in HIV-infected individuals are warranted.